ANALYSIS OF CONSUMER PERCEPTION THROUGH THE BRAND AMBASSADOR ‘FUJII-AN’ ON PURCHASE INTENTION OF PRODUCTS ON E-COMMERCE IN INDONESIA - Nurlaila Hasan; Darman; Ayu Anastasya Rachman (LP2M Universitas Bina Mandiri Gorontalo, 2026)
This study aims to analyze the effect of Consumer Perception on the Fujii-an Brand Ambassador, the effect of the Brand Ambassador on Purchase Intention, the effect of Consumer Perception on Purchase Intention, and the mediating role of the Brand Ambassador in the relationship between Consumer Perception and Purchase Intention. The study employed a quantitative research approach to examine the relationships among these variables. The population consisted of 1,000 consumers, while the sample comprised 150 respondents selected using purposive sampling techniques. Data were collected through observation and online questionnaires distributed to consumers who met the research criteria. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that Consumer Perception has a positive and significant effect on the Brand Ambassador (β = 0.390; t = 5.070; p = 0.000). Consumer Perception also has a positive and significant effect on Purchase Intention (β = 0.347; t = 4.363; p = 0.000). Furthermore, the Brand Ambassador positively and significantly influences Purchase Intention (β = 0.306; t = 3.629; p = 0.000). The mediation analysis reveals that the Brand Ambassador significantly mediates the relationship between Consumer Perception and Purchase Intention (β = 0.119; t = 2.905; p = 0.004). These findings demonstrate that favorable consumer perceptions contribute to stronger purchase intentions both directly and indirectly through the effectiveness of the Fujii-an Brand Ambassador. Therefore, companies should strengthen consumer perceptions and optimize brand ambassador strategies to enhance consumers' purchase intentions toward Fujii-an products.